Determining of PM 10 aqi over Malaysia using NOAA-14 AVHRR satellite data - Ahmad, Asmala; Hashim, Mazlan; Ayof, Mohd Nizam; Budi, Agus Setyo; Sakidin, Hamzah; S Ahmad, S. Sakinah (Universiti Utara Malaysia, 2005)
Particulate Matter sizing less than 10 micrometers or widely known as PM 10 is one of the major constituents of thick haze phenomenon, which occurred in Malaysia during September 1997. In this study, seven scenes of NOAA-14 AVHRR satellite data were acquired in order to determine and map PM 10 over Malaysia. Five location of air pollution station were chosen where PM10 was measured. Band 1 (wavelength of 0.58-0.68 micrometers) of NOAA-14 AVHRR satellite data were converted from digital numbers to reflectance prior deriving PM 10 information from the imagery. Cloud separation was then carried out by integrating both visual and thresholding technique. Relationship between the satellite reflectance and the corresponding PM 10 AQI (Air Quality Index) at the stations was established using linear regression model. The model was then used to map the concentration of PM10 over Malaysia. The result indicates that remote sensing technique using bands 1 of NOAA-14 AVHRR data was capable to determine and map PM 10 concentration quantitatively. Finally, accuracy was assessed using RMSE technique.